2013
DOI: 10.2169/internalmedicine.52.9204
|View full text |Cite
|
Sign up to set email alerts
|

Serial Tc-99m MAG3 Renography Evaluating the Recovery of Acute Kidney Injury Associated with Minimal Change Nephrotic Syndrome

Abstract: Acute kidney injury (AKI) is a well-recognized complication of minimal change nephrotic syndrome (MCNS). Previous reports support the concept that AKI associated with MCNS is reversible; however, information regarding the hemodynamic basis of AKI in MCNS is insufficient. We herein describe a case of AKI in a man with MCNS. In this case, monitoring the longitudinal changes in renal perfusion using serial Tc-99 m-MAG3 renal scanning was beneficial for evaluating the pathophysiological background associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In our study, however, we did not assess kidney binding, mainly because many of our animals showed decreased kidney function after LPS administration, a commonly seen phenomenon in SIRS and sepsis patients (sepsis-induced acute kidney injury (AKI)) (39). As a result of the secondary reduced glomerular filtration rate and tubular dysfunction in the kidneys, the effective excretion of our ligand and its metabolites was delayed, resulting in ligand retention in the parenchyma of the kidneys, as has been described with 99mTc-Mag3 scans (40). We thus assumed that the increased radioactivity in the kidneys four hours post-LPS likely reflects a combination of upregulated TSPO expression (due to inflammatory changes) and ligand retention within the renal parenchyma, and as such is unreliable as a measure of immune activation after LPS administration.…”
Section: F]dpa-714 Pet Image Analysismentioning
confidence: 75%
“…In our study, however, we did not assess kidney binding, mainly because many of our animals showed decreased kidney function after LPS administration, a commonly seen phenomenon in SIRS and sepsis patients (sepsis-induced acute kidney injury (AKI)) (39). As a result of the secondary reduced glomerular filtration rate and tubular dysfunction in the kidneys, the effective excretion of our ligand and its metabolites was delayed, resulting in ligand retention in the parenchyma of the kidneys, as has been described with 99mTc-Mag3 scans (40). We thus assumed that the increased radioactivity in the kidneys four hours post-LPS likely reflects a combination of upregulated TSPO expression (due to inflammatory changes) and ligand retention within the renal parenchyma, and as such is unreliable as a measure of immune activation after LPS administration.…”
Section: F]dpa-714 Pet Image Analysismentioning
confidence: 75%
“…AKI is a well-recognized complication of MCNS ( 6 , 7 ). The concurrent use of PSL and some immunosuppressive agents, including MZB and CyA, has been a therapeutic option for the MCNS patients in whom PSL treatment is not sufficient to achieve either a complete or partial remission ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%